2016
DOI: 10.3892/br.2016.700
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune vitiligo in rheumatic disease in the mestizo Mexican population

Abstract: Vitiligo is a chronic disease characterized by the dysfunction or destruction of melanocytes with secondary depigmentation. The aim of the present study was to determine the prevalence of vitiligo associated with autoimmune rheumatic diseases. The clinical records from a 10-year database of patients with rheumatic diseases and associated vitiligo was analysed, with one group of patients having autoimmune rheumatic disease and another non-autoimmune rheumatic disease. Available serum samples were used to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It is a relatively common disorder, with a prevalence rate of 0.2–1% . Although the exact aetiology of vitiligo remains elusive, autoimmunity is believed to play an important role in disease pathogenesis, as vitiligo is often associated with autoimmune diseases . There is also evidence for a direct role for interferon‐γ‐producing CD8+ cytotoxic T lymphocytes (CTLs) in the progression of vitiligo, corresponding to a T helper (Th)1 response .…”
Section: Introductionmentioning
confidence: 99%
“…It is a relatively common disorder, with a prevalence rate of 0.2–1% . Although the exact aetiology of vitiligo remains elusive, autoimmunity is believed to play an important role in disease pathogenesis, as vitiligo is often associated with autoimmune diseases . There is also evidence for a direct role for interferon‐γ‐producing CD8+ cytotoxic T lymphocytes (CTLs) in the progression of vitiligo, corresponding to a T helper (Th)1 response .…”
Section: Introductionmentioning
confidence: 99%
“…In the end, the cells become fragmented and release apoptotic bodies. [31][32][33] However, in addition to apoptosis, several authors have recently suggested that neoantigens can also be caused by another form of melanocyte cell death such as necroptosis, pyroptosis, ferroptosis, oxeiptosis, and parthanatos, which are characterized by an inflammatory process. Apoptosis that is too long can also cause necrosis and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…One putative mechanism relates to the epitope spreading phenomenon, which occurs when the primary autoimmune process against SSc‐related epitopes leads to exposure of nearby epitopes, resulting in an autoimmune response against melanocytes and vice versa 28 . This mechanism is substantiated by the fact that anti‐melanocyte autoantibodies were found in 92% of individuals with multiple autoimmune rheumatic diseases 29 . Moreover, there is growing evidence that dermal fibroblasts, the effector cells of fibrosis in SSc, exert an important role in physiological pigmentation and pigmentary abnormalities 30,31 .…”
Section: Discussionmentioning
confidence: 99%